Heritage, memory & identity - Anheier, Helmut K., 1954-; Isar, Yudhishthir Raj. (Thousand Oaks, Calif. : SAGE Publications, 2011)
'Heritage, memory, and identity are closely connected keywords of our time, each endowed with considerable rhetorical power. Different human groups define certain objects and practices as'heritage'; they envision heritage to reflect some form of collective memory, either lived or imagined; and they combine both to construct cultural identities. Today, the three terms raise conjoined issues of practice, policy and politics in an increasingly globalized world. Bringing together a truly global range of scholars, this volume explores heritage, memory, and identity through a diverse set of subjects, including heritage sites, practices of memorialization, museums, sites of contestation, and human rights.'--Publisher description.
Includes bibliographical references and index.
Keywords: Culture and globalization; Arts and globalization